BENTUK, FUNGSI DAN MAKNA MOTIF PADA PAKAIAN ADAT BUNDO KANDUANG DI KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - YOVI KURNIATI, Drs. Efrizal, M.Pd., Dra. Jupriani, M.Sn (Serupa The Journal of Art Education, 2018)
This research has a purpose to describe: 1)form, 2)function, 3)meaning of motif on traditional clotihing Bundo Kanduang in Gunung Talang Subdistrict. This type of research is qualitative with descriptive approach. Primary data sources are told directly by informants, data sources taken in the form of written notes (recording, picture) which is gotten from the informant by doing the interview, documentation, and literature study. Motif comes from flora, fauna, and geometrical. The function of motif consist of personal, physical, and social. The meaning of motif describes the life of Minangkabau society.Kata kunci: Motif, Bentuk, Fungsi, Makna